Effective group discussion : theory and practice - Galanes, Gloria J.; Adams, Katherine (McGraw-Hill, 2013)
Combines the recent research findings and practical tools students need to become productive group members. This title covers work groups, committees, task forces, self-directed work teams, and other small groups whose objectives include finding solutions to problems, producing goods, and creating policies